Kemiskinan di Indonesia Demi Meningkatkan Pertumbuhan Ekonomi - Muhammad Yasin; Yeny Novita Fitriani; Joanne Andre Toy Penga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Poverty is one of the fundamental problems that is the center of attention of governments in any country. In almost all developing countries, the living standards of the majority of the population tend to be very low, not only when compared with the living standards of people in rich countries, but also with those of the elite in their own countries. This low standard of living is manifested in the form of very low levels of income or poverty (Todaro, 2006). Economic growth is believed to have a significant influence on reducing the amount of poverty. However, this influence may differ from one country to another. The state of income distribution, population, and urbanization have an important relationship in determining the influence that occurs between economic growth and reducing the amount of poverty (Hasan and Quibria, 2002).